PERHITUNGAN HARGA POKOK PRODUK PADA PERCETAKAN ARIES SAMARINDA - EKA YUDHYANI, TEGUH SETIAWAN, TITIN RULIANA, (EKONOMIA, 2016)
Teguh Setiawan, calculation of the cost of products using the cost method of printing orders at Samarinda aries under the guidance of a mentor mother Eka Yudhyani II, and mother Titin Ruliana as mentors I.The purpose of the research study aims to evaluate the application of the method of determining the cost of production used by ARIES Printing Samarinda as the determination of their selling price. The initial assumption there is that the use of methods that are still very simple used by business owners are not yet optimal, so that when it happens, this research also tries to provide one-step calculation of Cost of Production (HPP) and based on the data available and compare it with the Cost of Production (HPP) used by the company in determining the selling price of products.Based on the analysis and discussion To find the difference BOP can be done by reducing the number of factory overhead costs charged Rp. 8.93945 million, - that we can be of direct labor wages multiplied by 130% to the total cost of the actual factory overhead that occurs in the plant amounted to Rp. 6,715,789, - which comprises the use of adjuvant dart, indirect labor costs, overhead costs more. Then we can determine the amount of the difference BOP Rp. 2,223,661, -.With the reduction of the total sales of Rp. 42.6275 million, - the calculation of the cost of products using the order cost Rp. 27,043,250, - and the profit earned after deducting advance with BOP difference that we calculated above Rp. 2,223,661, -, then we can calculate Gross Profit and Loss-orders for the entire product is Rp. 17,807,911, - This amount is larger than the gross profit calculation previously calculated by the company in the amount of Rp. 13.02625 million, -. And the amount of calculation of the cost of products by using the order cost is Rp. 27.04325 million, - more favorable than the previous calculation is Rp. 29.60125 million, -. Thus the hypothesis that the writer suggested in the previous chapter can be accepted.